(untitled) (Research, Society and Development, 2023)
Mining is an important activity, however it can cause negative environmental and social impacts. A large company in the mining sector, AngloGold, located in the municipality of Santa Bárbara, MG, was questioned regarding the possible release of industrial effluents into water resources close to its complexes. To understand the environmental impact caused and its magnitude, the chemical specification of environmental matrices, such as sediment, can be used, which promotes a more dynamic interpretation of the real impact and measures the toxicity indices at the analysis points, as well as the bioavailability of chemical species in the environment. Thus, the objective of this work was to carry out metal speciation in the sediments of the Conceição River, close to the Córrego ao Sítio Mine, belonging to AngloGold. Regarding the focus, this research is quantitative and regarding technical procedures, the research is experimental. The samples were collected in the region of Barra Feliz, São Bento and Brumal. The BCR-701 sequential removal procedure was used for the study. An increase in concentration is confirmed, at the company point (P2), in the exchangeable fraction, considered more mobile and available. Metal and semi-metal contents do not fall outside the limits established by CONAMA 454/2012, with the exception of Zn, which has a concentration of 155.86 mg.kg-1 in P4. It was found that the most mobile metal is Zn, evaluated by the Mobility Factor of the element in an aquatic environment. It is stated that the quantified metals are harmful to the environment and the health of men and animals, as they contain pseudo-total concentrations above the possible limit established by legislation.